Assessment of Concentration and Ecological Risks of some Persistent Organochlorine Compounds in Water and Sediments of the Red River Running from Hanoi to Nam Dinh - Tham, Trinh Thi; Thuy, Trinh Thi; Trung, Nguyen Thanh; Trinh, Le Thi (VNU Journal of Science: Natural Sciences and Technology, 2022)
This study focuses on the assessment of organochlorinated pesticide (OCPs) and polychlorinated biphenyls (PCBs) concentrations in water and surface sediments in the Red River flowing from Hanoi to Nam Dinh city with a length of 85 km. Fifteen paired water and surface sediment samples were collected and analyzed for the concentrations of OCPs and PCBs by GC-ECD. The total concentrations of PCBs, HCHs, DDTs and OCPs in water samples were ranged from 0.013 ÷ 0,033 µg/L; 0.601 ÷ 30.7 µg/L; 0.091 ÷ 2.73 µg=/L and 1.27 ÷ 39.3 µg/L, respectively. The average residue levels of these substances in sediment samples were 23.3 µg/kg dry weight (dw), 14.6 µg/kg dw, 1.16 µg/kg (dw), and 18.2 µg/kg (dw), respectively. Semi-quantitative risk assessment indicates that OCPs in water and surface sediments in the study area were low to moderate risk. The obtained data can be a scientific basis for implementing environmental pollution control measures in the Red River basin.